Perbandingan Daya Dukung Tiang Pancang berdasarkan Uji Kalendering dan Pile Driving Analyzer (PDA) pada Pekerjaan Penggantian Jembatan Sei. Rengas Jambi - Raudhati, Emelda (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to compare the bearing capacity based on the calendaring test and Pile Driving Analyzer (PDA) on the replacement work of the Sei. Rengas Jambi Bridge. The calendaring test is calculated using the Hiley formula while the PDA test uses the case method and CAPWAP analysis according to ASTM D4945. The results of the study show that there are significant differences between the two methods, namely the average calendaring bearing capacity of 279.33 tons with a standard deviation of 109.43 tons, while the average PDA bearing capacity is 203.5 tons with a standard deviation of 66.5 tons. The range of calendaring values provides higher bearing capacity results.